Gestão na atenção pré-hospitalar de urgência do município de Goiânia-GO - Moraes, Patrícia Antunes de (2012)
The study represents a search for data and facts that support the issues that underlie the management of public health services, specifically regarding to the management of units of pre-hospital emergency being addressed mobile and fixed components. The eighteen studied units represent a 24 hours open door, ready to admit the spontaneous demands at all levels of clinical severity, whether traumatic, pediatric, obstetric, and psychiatric, among others. A descriptive exploratory research has been held with managers from units of pre-hospital care in Goiânia in 2010 and 2011. Eighty-four managers have participated in the study, representing all the professionals involved in this activity in the services of pre-hospital emergency. The results demonstrate the potential and challenges experienced by those managers and the management tools used. Regarding to the practice in the management, planning has been used as an essential technology and needed to qualify the management process. The potential presented by the research as needed characteristics to the contemporary management to reach the proposals from both the Ministry of Health as the current literature in the area of administration of health services.